Pengaruh Online Customer Rating, Online Customer Review, Cash On Delivery (COD), dan Gratis Ongkos Kirim Terhadap Keputusan Pembelian di E-Commerce Lazada - Rohmah, Mimmatur; Rizal, Mohammad; Athia, Ita (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to determine and analyze the effect of online customer rating, online customer review, cash on delivery, and free shipping on purchasing decisions on Lazada e-commerce. This research uses case studies on active students of the Faculty of Economics and Business, Islamic University of Malang who were selected by purposive sampling. Determination of the number of samples using the Malholtra formula and the results obtained were 80 respondents. Data analysis methods used in this study are Instrument Test (validity test and reliability test), Normality Test, Classical Assumption Test (multicollinearity test and heteroscedasticity test), Multiple Linear Regression Analysis, Hypothesis Test (F test and t test), and Determination Coefficient Test (Adjusted R2). Process analysis using SPSS. The results of the study state that online customer rating, online customer reviewy, cash on delivery, and free shipping simultaneously influence purchasing decisions and partially online customer rating, online customer review, and free shipping have a positive and significant effect on purchasing decisions. While cash on delivery has not significant effect on purchasing decisions. Keywords: Online Customer Rating, Online Customer Review, Cash On Delivery, Free Shipping, and Purchase Decision